Comparative long‐term outcomes of laparoscopic hepatectomy and radiofrequency ablation for hepatocellular carcinoma located in the anterolateral segments of the liver. (2nd November 2021) - Kim, Sungho; Yoon, Chang Jin; Cho, Jai Young; Han, Ho‐Seong; Yoon, Yoo‐Seok; Lee, Hae Won; Lee, Jun Suh; Kim, Moonhwan; Lee, Boram; Ahn, Soyeon
Abstract: Background: Laparoscopic liver resection (LLR) is considered the standard surgical approach for resecting small hepatocellular carcinomas (HCC) located in the anterolateral segments of the liver. However, few studies have compared LLR and radiofrequency ablation (RFA) in such cases. Methods: We retrospectively compared the short‐ and long‐term outcomes of 101 patients who underwent LLR and 264 patients who underwent RFA because of a newly diagnosed single, small (≤4 cm) HCC located in the anterolateral segments of the liver. By applying 1:1 propensity score matching, we matched 61 patients in both groups. Results: Although the 5‐year overall survival rates were similar (83.6% vs 84.5%; P  = .913), the 5‐year disease‐free survival rate was greater in the LLR group (56.4% vs 41.8%; P  = .009). In patients with an α‐fetoprotein level of ≥100 ng/mL, the 5‐year overall (100% vs 80.0%; P  = .022) and disease‐free survival (76.6% vs 45.5%; P  = .006) rates were greater in the LCC group. Conclusions: For patients with a single, small HCC located in the anterolateral segments of the liver, LLR was associated with similar complication and overall survival rates, but better disease‐free survival compared with RFA. LLR may be recommended for patients with higher α‐fetoprotein levels. Abstract : Highlight Laparoscopic liver resection for a single, small hepatocellular carcinoma in the anterolateral segment is an effective procedure and offers potential oncologic benefits. Kim and colleagues conclude that, in patients with an α‐fetoprotein level of ≥100 ng/ml, laparoscopic liver resection is recommended over radiofrequency ablation due to its favorable oncologic outcomes.